2020
DOI: 10.1039/d0dt00042f
|View full text |Cite
|
Sign up to set email alerts
|

Peroxocobalt(iii) species activates nitrilesviaa superoxocobalt(ii) diradical state

Abstract: The dioxygenation of nitriles by [CoIII(TBDAP)(O2)]+ (TBDAP = N,N-di-tert-butyl-2,11-diaza[3.3](2,6)-pyridinophane) is investigated using DFT-calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 71 publications
1
23
0
Order By: Relevance
“…12e,f Recently, we reported the distinct reactivity of a side-on peroxocobalt(III) complex, [Co III (TBDAP)(O 2 )] + (1), which reacts with nitriles to give hydroximatocobalt(III) complexes, [Co III (TBDAP)(R−C( NO)O)] + (R = Me (3), Et, and Ph). 13,14 In the present work, we report that mononuclear peroxocobalt(III) complex 1…”
Section: ■ Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…12e,f Recently, we reported the distinct reactivity of a side-on peroxocobalt(III) complex, [Co III (TBDAP)(O 2 )] + (1), which reacts with nitriles to give hydroximatocobalt(III) complexes, [Co III (TBDAP)(R−C( NO)O)] + (R = Me (3), Et, and Ph). 13,14 In the present work, we report that mononuclear peroxocobalt(III) complex 1…”
Section: ■ Introductionmentioning
confidence: 58%
“…Recently, we reported that the reactive form of 1 capable of activating nitrile substrates consists of a triplet Co­(II)-superoxo species, [Co II (TBDAP)­(O 2 – )] + , when M n + is not present. As shown in Figure , 1 can bind a nitrile substrate via the transition state 1-TS at 12.3 kcal mol –1 to give intermediate A .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations